Показатель инфракрасной заметности боевых летательных аппаратов для оценки влияния конструктивно-компоновочных решений на заметность - Анипко, О. Б.; Украинец, Е. А. (НТУ "ХПИ", 2009)
The task of conformity of definite tactics-technical characteristics at the maximally possible descent of level of all types of viewing, including, infra-red stands before a developer during the multiple researches of arrange-ments of battle aircrafts. The index of infra- red viewing of battle aircrafts is developed for estimation of the structural-arrangement decisions accepted on the initial stage of the aircraft synthesis. The interconnection of radio- location and infra-red viewing is shown; analytical expression of connection of their indexes is got.
Keywords: военная авиация; воздушная цель; инфракрасное излучение; теплопеленгационная система; летательный аппарат; собственное излучение; излучение фона; двигатель реактивный; реактивная струя; планер